1992
DOI: 10.1007/bf02535582
|View full text |Cite
|
Sign up to set email alerts
|

Borage or primrose oil added to standardized diets are equivalent sources for γ‐linolenic acid in rats

Abstract: The aim of this study was to evaluate the effect of different doses and sources of dietary gamma-linolenic acid (GLA) on the tissue phospholipid fatty acid composition. Rats fed four different levels of GLA (2.3, 4.6, 6.4 and 16.2 g of GLA/kg diet) in the form of either borage oil or evening primrose oil during 6 wk were compared with animals fed corn oil. The levels of dihomo-gamma-linolenic acid (DHLA) and GLA showed a significant dose-related increase in liver, erythrocyte and aorta phospholipids. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 48 publications
3
5
0
2
Order By: Relevance
“…As noted above, the n-3/ n –6 fatty acid ratio in the HGSO diet was higher and thus the n –3 fatty acids could have suppressed the delta-6 desaturase activity thereby decreasing the production of 22:5 n –6. Similar changes in 22:5 n –6 have been reported by others who also fed equal amounts of 18:3 n –6 but with higher n –3 fatty acids (Palombo et al, 2000; Raederstorff and Moser, 1992). The amount of 22:5 n –6 however, represents only a minor fraction of the overall fatty acid composition of tissue phospholipids.…”
Section: Discussionsupporting
confidence: 86%
“…As noted above, the n-3/ n –6 fatty acid ratio in the HGSO diet was higher and thus the n –3 fatty acids could have suppressed the delta-6 desaturase activity thereby decreasing the production of 22:5 n –6. Similar changes in 22:5 n –6 have been reported by others who also fed equal amounts of 18:3 n –6 but with higher n –3 fatty acids (Palombo et al, 2000; Raederstorff and Moser, 1992). The amount of 22:5 n –6 however, represents only a minor fraction of the overall fatty acid composition of tissue phospholipids.…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings were reported by Raederstorff and Moser in a GLA feeding study comparing BO with primrose oil (14). They found no changes in liver GLA and DHGLA levels within groups given equal amounts of dietary GLA from either oil source, indicating that the relative percentages of GLA and DHGLA in tissue phospholipids are dependent upon the GLA content in the diet, but not on the oil source of GLA.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, preferential binding of n-3 vs. n-6 fatty acids at this later ∆6 desaturation step would result in decreased production of 22:5n-6 as observed in the liver phospholipids for the HGCO group. Similar changes in 22:5n-6 have been reported by others who also fed diets with equal amounts of GLA, but unbalanced n-3/n-6 fatty acids (14). It should be noted, however, that the level of 22:5n-6 represents only a minor fraction of the overall PUFA content in liver lipids.…”
Section: Discussionsupporting
confidence: 67%
“…Dietary studies have demonstrated that changes in the profile of highly unsaturated fatty acids in the lipids of various tissues can be achieved by varying the absolute and relative amounts of LA and GLA in the diet (Dutta-Roy, 1993). Direct supplementation with GLA is extremely costly, therefore most of the research in this area has used oils from the seeds of flowering plants as crude sources of GLA such as borage, evening primrose, and sunflower (Singer et al, 1990;Raederstorff and Moser, 1992). Evening primrose oil (EPO) has become the most popular of these oils because of its high GLA content which is approximately 15% (Gibson et al, 1992).…”
Section: Diabetes-induced Metabolic Defects: Importance Of Hyperlipidmentioning
confidence: 99%